Various methods of cooling sows in outside lots - D Ames; S Pollmann; G Francis; David A Nichols (Kansas Agricultural Experiment Station Research Reports, 1980)
Intermittent sprinkling in outside individual sow pens reduces the amount of water used to cool the sow without adversely affecting performance.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Cooling; Sows; Outside lots